Effects of liver depression and psychological stress on human uterine leiomyoma cells by an AR-cAMP-PKA signal transduction pathway - Tian Xia; Shuang Li; Ruihong Ma; Sufen Guan; Jiacui Li; Hongqin Li; Hexin Zhang; Qiu Lin; Zhimei Zhao; Baojuan Wang (Elsevier, 2017)
Objective: Based on the emotional theory of Traditional Chinese Medicine, and combined with the modern medicine theory of psychological stress, a research model of human uterine leiomyoma cells (ULM) was cultured in vitro to determine the effectiveness of adrenergic receptor (AR) agonists in human ULM cell growth. In addition, we studied the functional influence of "liver depression and psychological stress theory" on fibroid formation by intervening in the AR-cAMP-PKA signaling pathway. The intention was to establish a new method to prevent and cure fibroids through "liver depression and psychological stress theory" and provide an experimental basis for the Traditional Chinese Medicine emotional theory. Materials and methods: Primary human ULM cells were enriched by collagenase digestion. Immunohistochemistry and hematoxylin and eosin (HE) staining were used for cytological identification. Using this model, we studied intervention using specific AR agonists on ULM cells to observe the influence of "liver depression and psychological stress theory" on estrogen receptor (ER), progesterone receptor (PR), vascular endothelial growth factor (VEGF) and fibroblast growth factors (FGF). Results: Norepinephrine (NE) and epinephrine (E) are adrenergic receptor agonists. They promoted ULM cell proliferation and increased the levels of ER, PR, VEGF and FGF. In contrast, isoproterenol (ISO) inhibited ULM cell proliferation and decreased the levels of ER, PR, VEGF and FGF. The protein expression of cAMP and PKA in ULM cells was reduced and the levels of ER, PR, VEGF and FGF were increased when co-treatment with the α-AR blocker (phentolamine). The β-AR blocker (metoprolol) displayed an opposite effect. Conclusions: AR agonists modulated ER, PR, VEGF and FGF levels in ULM cells in an AR-cAMP-PKA-dependent signaling pathways to influence fibroid occurrence and development.